Implementasi Pendidikan Karakter Pendekatan Tasawuf (Studi Kasus Pondok Pesantren Jagad ‘Alimussirry) - Anwar, Ulil; Lutfauziah, Asmaul; Hartono, Djoko (Journal Intellectual Sufism Research (JISR), 2021)
This study aims to: (1) find out the application of Sufism-based character education in PPJA, (2) find out how to implement Sufism education in PPJA, and (3) know the importance of Sufism education in shaping the character of students in PPJA. This type of research is qualitative research with a case study approach. The results showed: (1) Character education with a Sufism approach has been implemented at PPJA, (2) Implementation of character education is adjusted to the tirakatan curriculum and behaviour at PPJA, and (3) The importance of Sufism education in character building to educate students to become Muslim scholars lover/guardian of Allah and the character that is expected to be contextualized in life in society